One Love : A Pastoral Guide to The Order of Celebrating Matrimony - Turner, Paul, 1953- (Book collections on Project MUSE., 2016)
"The publication of the second edition of The Order of Celebrating Matrimony provides new liturgical and pastoral opportunities for presiders and parishes. In One Love, Fr. Paul Turner--one of the most reliable experts in Catholic liturgy today--provides sound guidance and instruction on the rite. Among the many important and practical topics he covers are: uses for the expanded introduction; the engagement ceremony; the location for the wedding; the revised words for the questions, consent, and reception of consent; the customs of the arras, the lazo, and the veil; other wedding customs; and more."--Publisher description.